Regulation of gene expression in Dictyostelium discoideum cells exposed to immobilized carbohydrates - Bozzaro, Salvatore (1984)
When amoebae of Dictyostelium discoideum develop on gels of polyacrylamide that are derivatized with glucosides, they become capable of aggregation at the same time as cells not exposed to glucosides. However, the aggregation centers and streams of adherent cells formed on immobilized glucosides suddenly disintegrate. The cells repeatedly re-aggregate, but never form tight aggregates as they do on other substrata. Tight aggregates formed in the absence of glucosides disperse after their transfer to glucoside gels, and the cells undergo aggregation-disaggregation cycles. The formation of tight aggregates is correlated with the expression of specific post-aggregative poly(A)(+) RNAs. These RNAs are not expressed in cells developing on glucoside gels, and the dispersal of tight aggregates on such gels is accompanied by the almost complete loss of these RNAs. A developmentally regulated membrane glycoprotein called contact site A, which is a marker of aggregation-competent cells, is normally expressed on glucoside gels. Cyclic AMP is also produced, indicating that the strong increase of adenylate cyclase activity during the preaggregation phase is not affected. In conclusion, cell contact with immobilized glucosides specifically inhibits postaggregative gene expression and arrests development at the aggregation stage.